Rural Poverty and Credit Use: Evidence from Pakistan (The Pakistan Development Review, 1999)
The 1990s have seen poverty reduction become the overarching objective of all economic development. In countries where poverty is largely a rural phenomenon it is obvious that considerations of poverty focus on improving rural welfare. The welfare impact of credit use in the process of agricultural development is generally not explicitly documented in the literature.1 The emphasis is generally on “the requisites for development of rural financial policies that facilitate rural growth” [Desai and Mellor (1993)]. Welfare gains arise from this growth through net gains in income from the relaxation of the capital constraint leading to higher input use and resultant higher output, in addition to increasing the risk bearing capacity of households thus leading to the adoption of new technology and diversification of crop mix and income sources. Additionally welfare gains can also arise from credit use directly through improved and more efficient consumption smoothing. Pakistan is predominantly rural and poor. Attempts over several decades, by successive governments, at developing the institutional credit market in Pakistan have failed miserably. The rural credit market continues to be fragmented and beset by distortions. Credit policy aimed at improving access of the small landowners and the poor ended up being diverted to the powerful large landowners. This misuse is widely documented in Malik (1989, 1990 and 1999). Badly designed policies coupled with a weak institutional structure and rampant corruption called into question the very basis for using credit markets as a means for poverty alleviation.